Synergistic typhoid and taenia solium intestinal perforation. - Ashwani, K; Pankaj, KG; Divya, S; Paras, KP; Vijay, KS (Department of Surgery, UKM Medical Centre, 2013)
Typhoid and intestinal infestation with parasites are common and may co-exist especially in the tropics. Their synergistic acute abdominal presentation is rare. We here report a 38-year-old male who presented with complaints suggestive of enteric fever and signs of peritonitis. Following baseline investigations, laparotomy was performed which proved to be a surgical surprise. A live tape worm was seen pouting out of the terminal ileal perforation. The clinical presentation and the stringent attention to preventive measures are discussed.